2022
DOI: 10.3390/metabo12111012
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Geographical Origin of White and Brown Rice Samples Using NMR Spectroscopy Coupled with Machine Learning Techniques

Abstract: Rice (Oryza sativa L.) is a widely consumed food source, and its geographical origin has long been a subject of discussion. In our study, we collected 44 and 20 rice samples from different regions of the Republic of Korea and China, respectively, of which 35 and 29 samples were of white and brown rice, respectively. These samples were analyzed using nuclear magnetic resonance (NMR) spectroscopy, followed by analyses with various data normalization and scaling methods. Then, leave-one-out cross-validation (LOOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…116,117 Previous studies revealed that the application of ML in the analysis of NMR data is not rare, but most of these applications tend to solve the classification problem based on the fingerprint information carried by NMR combined with the ML algorithms, and do not focus on the structure elucidation. 118–120 By conducting a comprehensive literature review, we have classified the ML algorithm-aided NMR data-based NPs structural analysis methods into three distinct categories: (i) ML-assisted annotation of functional groups; (ii) ML-assisted classification of NPs; and (iii) ML-assisted quantum chemical calculation NMR.…”
Section: In Nmr-based Nps Analysismentioning
confidence: 99%
“…116,117 Previous studies revealed that the application of ML in the analysis of NMR data is not rare, but most of these applications tend to solve the classification problem based on the fingerprint information carried by NMR combined with the ML algorithms, and do not focus on the structure elucidation. 118–120 By conducting a comprehensive literature review, we have classified the ML algorithm-aided NMR data-based NPs structural analysis methods into three distinct categories: (i) ML-assisted annotation of functional groups; (ii) ML-assisted classification of NPs; and (iii) ML-assisted quantum chemical calculation NMR.…”
Section: In Nmr-based Nps Analysismentioning
confidence: 99%